HUBUNGAN KEKUATAN OTOT LENGAAN-BAHU DAN KELENTURAN PUNGGUNG DENGAN HASIL LEMPAR CAKRAM PADA SISWA KELAS XI SMAN 2 UJUNG TANJUNG KECAMATAN TANAH PUTIH - Yon Maryono; Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the low throwing results of the students of SMAN 2 Ujung Tanjung. Of KKM targeted not all students are able to achieve. This problem can be seen from the observation of researcher during school learning, it is suspected because of the arm-shoulder muscle strength and back flexibility owned by students. Therefore, the purpose of this study was to determine the corelation between strength arm-shoulder muscles and back flexibility with disc throw results students class XI SMAN 2 Ujung Tanjung. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is a trength arm-shoulder muscles, (X2) back flexibility, while the dependent variable (Y) is the disc throw results. The research data was obtained from the measurement results using flexiometer, expanding dynamometer test and discus throwing. The sample in this study were male students of SMAN 2 Ujung Tanjung who totaled 35 people (total sampling). Based on the research results can be concluded as follows: From the results obtained strength of arm shoulders muscles have a corelation with the results of discus throwing at SMA Negeri 2 Ujung Tanjung Tanah Putih, where rhitung (0375)> rtabel (0.334) at α = 0 05. From the results obtained flexibility of the waist have a corelation with the discus throwing results at SMA Negeri 2 Ujung Tanjung Tanah Putih, where rhitung (0384)> rtabel (0.334) at α = 0.05. An corelation was jointly between strength shoulder arms muscle and back flexibility with discus throwing results of at SMA Negeri 2 Ujung Tanjung Tanah Putih, where rhtung (0485)> rtabel (0.334) at α = 0.05.Keywords : Strength Arm- Shoulder Mucles, Disc Throwing